Historical perspectives to postglacial uplift : case studies from the Lower Satakunta Region /: case studies from the Lower Satakunta Region. ([2019]) - Pohjola, Jari; Turunen, Jari; Lipping, Tarmo; Sivula, Anna; Marila, Marko
No abstract available